2016
DOI: 10.1159/000446183
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Exacerbation of Asthma Is Frequently Associated with Recurrent Episodes of Acute Urticaria

Abstract: Background: Asthma and urticaria are both partially mediated by an increased release of histamine from highly activated mast cells. They are pathophysiologically different, as mast cell degranulation in these 2 disorders results from different mechanisms. Objective: To assess the incidence of urticaria in patients with asthma, and of asthma in patients with chronic spontaneous urticaria (CSU). Patients and Methods: Over 1 year of follow-up, asthma patients (n = 110) were assessed for the incidence and characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…All the 8 patients with asthma in our study had positive SPT and all of them had AR meaning that they had allergic asthma, which is in line with other studies showing that seasonal exacerbation of allergic asthma can trigger recurrent episodes of acute urticaria [ 13 ], but joint autoimmune mechanism is the most likely cause of asthma in CSU [ 14 ]. Almost all the patients with atopic dermatitis (AD) had negative SPT at the same time, which is compatible with non-IgE mediated pathophysiology of AD and again autoimmune mechanism can be the cause of this co-morbidity [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All the 8 patients with asthma in our study had positive SPT and all of them had AR meaning that they had allergic asthma, which is in line with other studies showing that seasonal exacerbation of allergic asthma can trigger recurrent episodes of acute urticaria [ 13 ], but joint autoimmune mechanism is the most likely cause of asthma in CSU [ 14 ]. Almost all the patients with atopic dermatitis (AD) had negative SPT at the same time, which is compatible with non-IgE mediated pathophysiology of AD and again autoimmune mechanism can be the cause of this co-morbidity [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…trigger recurrent episodes of acute urticaria [13], but joint autoimmune mechanism is the most likely cause of asthma in CSU [14]. Almost all the patients with atopic dermatitis (AD) had negative SPT at the same time, which is compatible with non-IgE mediated pathophysiology of AD and again autoimmune mechanism can be the cause of this co-morbidity [14].…”
Section: Medicine Consumptionmentioning
confidence: 99%
“…Another study in children also observed a strong association of urticaria with asthma, eczema, and hay fever [11] . It has been reported that acute urticaria is more common in patients with asthma and could be induced by exacerbation of seasonal asthma [26] . Raciborski et al [12] found that specific foods were important eliciting factors in 12.6% of patients with urticaria.…”
Section: Discussionmentioning
confidence: 95%
“…[26][27][28] Some studies have shown that asthma and urticaria are related and that asthma is common in patients with chronic spontaneous urticaria. 29,30 According to previous studies, 4,13 the IV seldomly causes extensive cutaneous or chronic adverse effects. However, the most frequently reported events are injection site transient reactions or nonspecific inflammation.…”
Section: Discussionmentioning
confidence: 97%